Propose A Training Program Based On Training Method (mixed - Repetitive) During The Competition Phase And Its Effectiveness To Developing The Speed For Football Players (u13) - Laidi , Abderrahim; Sedira , Saad (sports creativity, 2025)
The study aimed to find out the impact of the proposed training program in the competition stage on the development of the status of transitional speed among football players under the age of 13, and also to identify the differences between tribal and remote testing in the transitional speed status of the experimental group, and the researcher used the experimental approach with equal groups (officer and experimental), and the sample of the study was made up of 20 players under the age of 13 who were selected in a meaningful way. After conducting statistical treatment to verify the validity of the hypotheses, the results of the study showed the differences between the control and experimental groups in the remote test of transitional speed characteristic of football players under the age of 13, where the members of the experimental group outperformed the members of the control group in the remote test of the study.